2016
DOI: 10.1515/hsz-2015-0192
|View full text |Cite
|
Sign up to set email alerts
|

IsoQC (QPCTL) knock-out mice suggest differential substrate conversion by glutaminyl cyclase isoenzymes

Abstract: Secretory peptides and proteins are frequently modified by pyroglutamic acid (pE, pGlu) at their N-terminus. This modification is catalyzed by the glutaminyl cyclases QC and isoQC. Here, we decipher the roles of the isoenzymes by characterization of IsoQC-/- mice. These mice show a significant reduction of glutaminyl cyclase activity in brain and peripheral tissue, suggesting ubiquitous expression of the isoQC enzyme. An assay of substrate conversion in vivo reveals impaired generation of the pGlu-modified C-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In addition to pathogenic N-truncated Abeta peptides, there are also physiological QC substrates, such as neuropeptides and peptide hormones [ 39 , 40 ], that could be potentially affected by QC inhibition. However, in experimental animals with genetic QC ablation or pharmacological QC inhibition [ 41 , 42 , 43 ], it was found that the hypothalamic-gonadotropic and hypothalamic-thyroid axes, which are regulated by the QC substrates gonadoliberin (GnRH) and thyroliberin (TRH), are only marginally affected in presence of strong QC inhibition. Furthermore, in two clinical trials (see below), no effects on these hormone axes or other side effects with relation to QC substrates were observed, although a QC target occupancy in the brain of about 90% was reached under treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pathogenic N-truncated Abeta peptides, there are also physiological QC substrates, such as neuropeptides and peptide hormones [ 39 , 40 ], that could be potentially affected by QC inhibition. However, in experimental animals with genetic QC ablation or pharmacological QC inhibition [ 41 , 42 , 43 ], it was found that the hypothalamic-gonadotropic and hypothalamic-thyroid axes, which are regulated by the QC substrates gonadoliberin (GnRH) and thyroliberin (TRH), are only marginally affected in presence of strong QC inhibition. Furthermore, in two clinical trials (see below), no effects on these hormone axes or other side effects with relation to QC substrates were observed, although a QC target occupancy in the brain of about 90% was reached under treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A second QC in mammals is retained within the Golgi complex (isoQC) (15, 39). Differential cellular distribution of QC and isoQC may indicate a preference for different substrates in the secretory pathway and thus distinct physiological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Differential cellular distribution of QC and isoQC may indicate a preference for different substrates in the secretory pathway and thus distinct physiological roles. This has been demonstrated in monocyte chemoattractant proteins (MCPs) versus thyrotropin-releasing hormone (TRH) where only one QC is involved in the pGlu formation for each protein (39, 40). In N. crassa , both QC-1 and QC-2 localized primarily to the ER, where proteins with a liberated N-terminal Q or E would be cyclized to pGlu.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse primary neurons were isolated as described by Becker et al. (2015) . The cultivated cells were treated with freshly dissolved Aβ(1‐42) and pGlu‐Aβ(3‐42) at a final concentration of 5 μM for 69 h. Afterwards, MTT (3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyl tetrazolium bromide) has been added to the cell medium.…”
Section: Methodsmentioning
confidence: 99%